Immobilized cold-active enzymes onto magnetic chitosan microparticles as a highly stable and reusable carrier for p-xylene biodegradation - Miri, Saba; Ravula, Anupriya; Akhtarian, Shiva; Davoodi, Seyyed Mohammadreza; Brar, Satinder Kaur; Martel, Richard; Rouissi, Tarek (Frontiers in Environmental Engineering, 2024)
Stability and reusability properties are the two most important factors that determine an enzyme's application in industry. To this end, cold-active crude enzymes from a psychrophile (xylene monooxygenase (XMO) and catechol 1,2-dioxygenase (C1,2D) were immobilized on magnetic chitosan microparticles for the first-time using glutaraldehyde as a linker. The potential application of enzyme-loaded magnetic particles to remove and detoxify dissolved p-xylene from water confirmed the synergistic mechanism of degradation for in-situ bioremediation in soil and water. Immobilization was optimized based on four variables, such as magnetic particle (MPs), chitosan, glutaraldehyde, and enzyme concentrations. The immobilized enzymes were characterized by Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM). The immobilized enzymes showed improved pH tolerance ranging from 4.0 to 9.0, better temperature stability ranging from 5 to 50, higher storage stability (∼70% activity after 30 days of storage), and more importantly, reusability (∼40% activity after 10 repetitive cycles of usage) compared to their free form. Also, the immobilization of enzymes increased the effectiveness of the enzymatic treatment of p-xylene in soil (10,000 mg/kg) and water (200 mg/L) samples. As a result of the superior catalytic properties of immobilized XMO and C1,2D, they offer great potential for in situ or ex-situ bioremediation of pollutants in soil or water.